Early upregulation of kinin B(1) receptors in retinal microvessels of the streptozotocin-diabetic rat - Abdouh, Mohamed (2003)
1. Retinal microvessel responses to kinin B(1) and B(2) receptor agonists and antagonists were investigated in streptozotocin (STZ)-diabetic rats and age-matched controls. In addition, quantitative in vitro autoradiography was performed on retinas from control and STZ-diabetic rats with radioligands specific for B(2) ([(125)I]HPP-Hoe 140), and B(1) receptors ([(125)I]HPP-[des-Arg(10)]-Hoe 140). 2. In control rats, the B(2) receptor agonist bradykinin (BK, 0.1–50 nM) vasodilated retinal vessels in a concentration and time-dependent manner. This effect was completely blocked by the B(2) receptor antagonist Hoe140 (1 μM). In contrast, the B(1) receptor agonist des-Arg(9)-BK (0.1–50 nM) was without effect. 3. Des-Arg(9)-BK was able to produce a concentration-dependent vasodilatation as early as 4 days after STZ injection, and the effect of 1 nM des-Arg(9)-BK was inhibited by the B(1) receptor antagonist des-Arg(10)-Hoe140 (1 μM). Low-level B(1) receptor binding sites were detected in control rats, but densities were 256% higher in retinas from 4- to 21-day STZ-diabetic rats. 4. In control rats, the vasodilatation in response to 1 nM BK involved neither calcium influx nor nitric oxide (NO) as GdCl(3) and L-NAME were without effect. However, the vasodilatation did involve intracellular calcium mobilization as well as products of the cyclooxygenase-2 (COX-2) pathway as 2,5-di-t-butylhydroquinone (BHQ), cADP ribose and L-745 337 inhibited this response. The vasodilatation response was blocked by trans-2-phenyl cyclopropylamine (TPC) demonstrating that prostacyclins mediate this response. 5. In STZ-diabetic rats, the vasodilatation in response to des-Arg(9)-BK involved both calcium influx and intracellular calcium mobilization from stores both IP(3) sensitive and non-IP(3) sensitive. Indeed, the effect was blocked by GdCl(3), BHQ and cADP ribose. Furthermore, NO production and products of the COX-2 pathway including prostacyclin are involved as the response was inhibited by L-NAME, L-745 377 and TPC. 6. Vasodilatation in response to either 1 nM BK or 1 nM des-Arg(9)-BK were blocked by NF023 demonstrating that a G(o)/G(i) G-protein transduces both these effects. 7. This is the first report on the retinal circulation which provides evidence for vasodilator B(2) receptors and the upregulation of B(1) receptors very early following induction of diabetes with STZ rats. These results suggest that kinin receptors may be potential targets for therapeutics to treat retinopathies.